CORPORATE SOCIAL RESPONSIBILITY STRATEGIES OF RESOURCE COMPANIES AS A DRIVER OF COMPETITIVENESS IN ARCTIC SINGLE-INDUSTRY TOWNS - Sergei V. Svinin; Vladimir V. Dyadik (Север и рынок: формирование экономического порядка)
This study examines national practices in implementing corporate social responsibility (CSR) strategies among resource companies as a means of enhancing not only corporate sustainability but also the socio-economic competitiveness of single-industry towns, or monotowns, in the Russian Arctic. Its scientific novelty lies in identifying the conditions that enhance competitiveness and uncover new sources of socio-economic development for Arctic single-industry towns through the collaborative engagement of all key stakeholders. Specifically, it is proposed that primary employers — resource companies — should play a more active role in this process by leveraging their social responsibility programs in the communities where they operate. The study employs a combination of qualitative and quantitative data analysis methods, including statistical, monographic, and descriptive approaches. The analysis is based on corporate reports from resource companies, official data from regional and municipal authorities, and national statistical sources. Findings indicate that CSR initiatives undertaken by resource companies contribute to the competitiveness of Arctic monotowns, particularly those reliant on mineral resource extraction. However, the study also reveals a misalignment between corporate CSR priorities and municipal development needs, as investments are primarily directed toward internal corporate social programs rather than broader community interests. Future research should focus on identifying the most effective approaches for aligning the strategies of primary employers and local governments to enhance the competitiveness and long-term sustainability of Arctic single-industry towns.